Impacts on Environmental Components of the Proposed Liquefied Petroleum Gas Bottling and Distribution Plant at Dacope Khulna in Bangladesh - Bagchi, R; Miah, MA; Islam, SMT; Shil, SC (Journal of Environmental Science and Natural Resources, 2019)
Impact identification is the first step in an Environmental Impact Assessment (EIA) process, contributing to prediction, evaluation and mitigation of significant environmental impacts. It connects the project characteristics to baseline environmental information with the aim of ensuring that all significant impacts are taken into consideration. The study location was at Dacope Upazila of Khulna District in Bangladesh. A Liquefied Petroleum Gas (LPG) bottling and distribution plant is going to set up by Energypac Power Generation Limited. The objective of the study was to identify the impacts on the major environmental components of the study area. The field observation, interviews of project proponent and community people, public consultation, laboratory analysis were the main activities of the study along with others. This study has done an appropriate analysis of baseline condition of the major environmental components of the study area, identified the impacts of the project on major environmental components and developed an environmental management plan for the LPG bottling and distribution plant. J. Environ. Sci. & Natural Resources, 11(1-2): 171-181 2018